Toward Community Empowerment: The Puerto Rican Ganchero. (March 2021) - Gelpí-Acosta, C.; Guarino, H.; Benoit, E.; Deren, S.; Rodríguez, A.
People who inject drugs (PWID) who migrate from Puerto Rico (PR) to New York City (NYC) are at elevated risk for hepatitis C (HCV), HIV and drug overdose. There is an urgent need to identify a sustainable path toward improving the health outcomes of this population. Peer-driven HIV/HCV prevention interventions for PWID are effective in reducing risk behaviors. Additionally, the concept of intravention —naturally occurring disease prevention activities among PWID (Friedman, 2004)—is a suitable theoretical framework to cast and bolster PWID-indigenous risk reduction norms and practices to achieve positive health outcomes. From 2017–2019, we conducted an ethnographic study in the Bronx, NYC to identify the injection risks of migrant Puerto Rican PWID, institutional barriers to risk reduction and solutions to these barriers. Study components included a longitudinal ethnography with 40 migrant PWID (e.g., baseline and exit interviews and monthly face-to-face follow-ups for 12 months), two institutional ethnographies (IEs) with 10 migrants and six service providers, and three focus groups (FGs) with another 15 migrant PWID. Data were analyzed using a grounded theory approach. In this article, we present findings from the IEs and FGs, specifically regarding a promising intravention pathway to promote health empowerment among these migrants that leverages an existing social role within their networks: the PR-indigenous ganchero . A ganchero is a vein-finding expert who is paid with drugs or cash for providing injection services. Ethnographic evidence from this study suggests that gancheros can occupy harm reduction leadership roles among migrant Puerto Rican PWID, adapting standard overdose and HIV/HCV prevention education to the specific experiences of their community. We conclude by noting the culturally appropriate risk reduction service delivery improvements needed to mitigate the health vulnerabilities of migrants and provide a roadmap for improving service delivery and identifying future research avenues.